THE CASE OF NEJVĚTŠÍ Z PIEROTŮ BY FRANTIŠEK KOŽÍK - Lukáš, Martin (Bohemica Olomucensia, 2021)
The paper is a case study on popular Czech biographical novel Největší z Pierotů by František Kožík published in 1939. After a concise context overview and a brief characterization of the novel, the study focuses on how the novel was received by the critics and what promotional strategy its publisher adopted, showing what was and what was not considered literary value in the Protectorate of Bohemia and Moravia.
Keywords: Největší z Pierotů; Jean Gaspard Deburau; František Kožík; Czech biographical novel; polemic